The Effect of Misalignment to Vibration, Electric Current and Shaft Rotation Speed on The Coupling Transmision - Romiyadi Romiyadi; Purnama Irwan (LP2M - Institut Teknologi Padang, 2020)
Coupling is one of the components are widely used in various industries. Coupling is widely used as a power transfer transmission. Coupling have a long life time, it mean coupling was damage if out of the maintenance. The one factor is misalignment. This study aim to determine the effect of misalignment on the coupling transmission to vibration, electric current and shaft rotation speed. In this study, was done alignment process with variations of misalignment on the coupling transmission and was done measurement value of vibration, electric current and shaft rotation speed. The study results show that the changed of misalignment would give a positive impact to vibration and electric current. For the effect misalignment to shaft rotation speed, the study results show that the changed of misalignment would give a negative impact to shaft rotation speed.